The effect of non‐oral hormonal contraceptives on hypertension and blood pressure: A systematic review and meta‐analysis - Cindy Z. Kalenga; Sandra M. Dumanski; Amy Metcalfe; Magali Robert; Kara A. Nerenberg; Jennifer M. MacRae; Zahra Premji; Sofia B. Ahmed (Physiological Reports, 2022)
Abstract Oral contraceptives (OC) are associated with increased risk of hypertension and elevated blood pressure (BP). Whether non‐oral hormonal contraceptives have similar associations is unknown. We sought to investigate the effect of non‐oral hormonal contraceptive (NOHC) use on the risk of hypertension and changes in BP, compared to non‐hormonal contraceptive and OC use. We searched bibliographic databases (MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials) until August 2020. Studies reporting risk of hypertension or changes in systolic and diastolic BP with NOHC use compared with either non‐hormonal contraceptive or OC use. Abstract screening, full‐text review, data extraction, and quality assessment were completed in duplicate. For studies reporting dichotomous outcomes, we reported results as relative risk with 95% confidence intervals (CI). A random‐effects model was used to estimate pooled weighted mean difference and 95% CI of change in BP. Twenty‐five studies were included. A lower incidence of hypertension was observed with injectable contraceptive use compared to non‐hormonal contraceptive and OC use, although it was unclear if this was statistically significant. Compared to non‐hormonal contraceptive use, injectable contraceptive use was associated with increased BP (SBP: 3.24 mmHg, 95%CI 2.49 to 3.98 mmHg; DBP: 3.15 mmHg, 95%CI 0.09 to 6.20 mmHg), the hormonal intra‐uterine device use was associated with reduced BP (SBP: −4.50 mmHg, 95%CI −8.44 to −0.57 mmHg; DBP: −7.48 mmHg, 95% −14.90 to −0.05 mmHg), and the vaginal ring was associated with reduced diastolic BP (−3.90 mmHg, 95%CI −6.67 to −1.13 mmHg). Compared to OC use, the injectable contraceptive use was associated with increased diastolic BP (2.38 mmHg, 95%CI 0.39 to 4.38 mmHg). NOHC use is associated with changes in BP which differ by type and route of administration. Given the strong association between incremental increases in BP and cardiovascular risk, prospective studies are required.